A Machine-Learning Approach for Dynamic Prediction of Sepsis-Induced Coagulopathy in Critically Ill Patients With Sepsis - Zhao, Qin-Yu; Liu, Le-Ping; Luo, Jing-Chao; Luo, Yan-Wei; Wang, Huan; Zhang, Yi-Jie; Gui, Rong; Tu, Guo-Wei; Luo, Zhe (Frontiers in Medicine, 2021)
Background: Sepsis-induced coagulopathy (SIC) denotes an increased mortality rate and poorer prognosis in septic patients. Objectives: Our study aimed to develop and validate machine-learning models to dynamically predict the risk of SIC in critically ill patients with sepsis. Methods: Machine-learning models were developed and validated based on two public databases named Medical Information Mart for Intensive Care (MIMIC)-IV and the eICU Collaborative Research Database (eICU-CRD). Dynamic prediction of SIC involved an evaluation of the risk of SIC each day after the diagnosis of sepsis using fifteen predictive models. The best model was selected based on its accuracy and area under the receiver operating characteristic curve (AUC), followed by fine-grained hyperparameter adjustment using the Bayesian Optimization Algorithm. A compact model was developed, based on 15 features selected according to their importance and clinical availability. These two models were compared with Logistic Regression and SIC scores in terms of SIC prediction. Results: Of 11362 patients in MIMIC-IV included in the final cohort, a total of 6744 (59%) patients developed SIC during sepsis. The model named Categorical Boosting (CatBoost) had the greatest AUC in our study (0.869; 95% CI: 0.850 to 0.886). Coagulation profile and renal function indicators were the most important features for predicting SIC. A compact model was developed with an AUC of 0.854 (95% CI: 0.832 to 0.872), while the AUCs of Logistic Regression and SIC scores were 0.746 (95% CI: 0.735 to 0.755) and 0.709 (95% CI: 0.687 to 0.733), respectively. A cohort of 35252 septic patients in eICU-CRD was analyzed. The AUCs of the full and the compact models in the external validation were 0.842 (95% CI: 0.837 to 0.846) and 0.803 (95% CI: 0.798 to 0.809), respectively, which were still larger than those of Logistic Regression (0.660; 95% CI: 0.653 to 0.667) and SIC scores (0.752; 95% CI: 0.747 to 0.757). Prediction results were illustrated by SHapley Additive exPlanations (SHAP) values, which made our models clinically interpretable. Conclusions: We developed two models which were able to dynamically predict the risk of SIC in septic patients better than conventional Logistic Regression and SIC scores.